2009
DOI: 10.1029/2008wr007207
|View full text |Cite
|
Sign up to set email alerts
|

Forests and floods: A new paradigm sheds light on age‐old controversies

Abstract: [1] The science of forests and floods is embroiled in conflict and is in urgent need of reevaluation in light of changing climates, insect epidemics, logging, and deforestation worldwide. Here we show how an inappropriate pairing of floods by meteorological input in analysis of covariance (ANCOVA) and analysis of variance (ANOVA), statistical tests used extensively for evaluating the effects of forest harvesting on floods smaller and larger than an average event, leads to incorrect estimates of changes in floo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
206
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(218 citation statements)
references
References 186 publications
4
206
0
2
Order By: Relevance
“…Assuming that the drivers included in the models can explain a large part of the natural variability of flow peaks, the detected change in the urbanizing catchment can be attributable solely to the increasing urban cover, in particular when compared to the unchanged patterns in the high flows of the rural paired catchment. Paired catchments have been widely employed in the assessment of the effects of changes in the catchment vegetation on river flow, in particular in forest hydrology [Brown et al, 2005;Alila et al, 2009]. In this study, the effects of the changes in land use on peak flows are investigated by assessing if any changes can be identified in the observed peak flows of the paired catchments.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the drivers included in the models can explain a large part of the natural variability of flow peaks, the detected change in the urbanizing catchment can be attributable solely to the increasing urban cover, in particular when compared to the unchanged patterns in the high flows of the rural paired catchment. Paired catchments have been widely employed in the assessment of the effects of changes in the catchment vegetation on river flow, in particular in forest hydrology [Brown et al, 2005;Alila et al, 2009]. In this study, the effects of the changes in land use on peak flows are investigated by assessing if any changes can be identified in the observed peak flows of the paired catchments.…”
Section: Introductionmentioning
confidence: 99%
“…The paired-catchment approach was applied to examine the effect of thinning on peak flow based on an assumption that rainfall and runoff responses between treatment and control catchments remained consistent during the pre-and post-thinning periods. Because the catchments were small (< 1 ha), storm events in control and treated catchment were similar in time, duration, intensity, or spatial extent (Alila et al, 2009). Additionally, the dominant internal hydrological processes were similar between the two catchments and remained consistent before and after treatments Dung et al, 2012).…”
Section: Hydrograph Analysismentioning
confidence: 95%
“…Analyzing the same data set, Thomas and Megahan (1998) demonstrated that peak runoff did not increase in large basins, but peak runoff in small basins increased 2-fold when comparing pre-and postharvesting periods. Reanalysis of these data were also conducted by Beschta et al (2000) and Alila et al (2009) to try to clarify these effects.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing local flooding risk by increased drainage increases flooding risk downstream, challenging the nested-scales management of watersheds to find an optimal spatial distribution, rather than minimisation, of flooding probabilities. Well-studied effects of forest conversion on peak flows in small upper stream catchments (Bruijnzeel, 2004;Alila et al, 2009) do not necessarily translate to flooding downstream. With most of the published studies still referring to the temperate zone, the situation in the tropics (generally in the absence of snow) is contested (Bonell and Bruijnzeel, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The statistical challenges of attribution of cause and effect in such data sets are considerable with land use/land cover effects interacting with spatially and temporally variable rainfall, geological configuration and the fact that land use is not changing in random fashion or following any pre-randomised design (Alila et al, 2009;Rudel et al, 2005). Hydrological analysis across 12 catchments in Puerto Rico by Beck et al (2013) did not find significant relationships between the change in forest cover or urban area, and change in various flow characteristics, despite indications that regrowing forests increased evapotranspiration.…”
Section: Introductionmentioning
confidence: 99%